DAMPAK PENGASUHAN ORANGTUA TERHADAP PERILAKU SOSIAL ANAK USIA DINI DI KECAMATAN INDRALAYA - Elsa Cindrya (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
The study aims to determine the parenting Impact of parents in Indralaya subdistrict. There are three Early childhood research samples, which are determined using the purposive sampling technique. Research Data collected through observations, interviews and documentation as well as subject field Records researched. Data is then analyzed through three stages: data reduction, data display and withdrawal or verification Conclusions. From the analysis, Indralaya was found a variety of foster patterns, including democratic, authoritarian, and permissive. But most have permissive patterns, because the parents to give freedom to the child, so that the child becomes uncontrolled while playing. Child social Behavior in the district of Indralaya tends to behave in a role, characterized by having socially brave traits by always playing outdoors without parental Supervision. And the impact of foster pattern on social behavior, early childhood in His ward will often do things without control or like it. Keywords: parenting, authoritarian, Democratic, permissive, Social behavior The study aims to determine the parenting Impact of parents in Indralaya subdistrict. There are three Early childhood research samples, which are determined using the purposive sampling technique. Research Data collected through observations, interviews and documentation as well as subject field Records researched. Data is then analyzed through three stages: data reduction, data display and withdrawal or verification Conclusions. From the analysis, Indralaya was found a variety of foster patterns, including democratic, authoritarian, and permissive. But most have permissive patterns, because the parents to give freedom to the child, so that the child becomes uncontrolled while playing. Child social Behavior in the district of Indralaya tends to behave in a role, characterized by having socially brave traits by always playing outdoors without parental Supervision. And the impact of foster pattern on social behavior, early childhood in His ward will often do things without control or like it.